The role of Primary Health Care in the access to legal abortion: international experiences - Melanie Noel Maia; Liana Wernersbach Pinto (Revista Brasileira de Saúde Materno Infantil)
Abstract Objectives: to analyze the clinical guidelines of countries that offer abortion in Primary Health Care (PHC), aiming to understand how the service delivery and the performance of PHC professionals occurs in different scenarios, to reflect on the viability of this offer in Brazil. Methods: narrative review carried out from the Global Abortion Policies Database platform, which gathers comprehensive information on abortion laws, regulations and clinical guidelines. Clinical guidelines from countries where abortion is performed at the first level of care were selected, in English, Spanish and Portuguese. Results: 26 countries were identified and 13 were included in the study. In general, abortion is performed in PHC in the first trimester, using medication or aspiration techniques, by different professional categories depending on the location, without the need for prior ultrasound. Conclusions: the study of international experiences shows that it is possible to provide abortion in PHC services using the existing workforce and structure, in accordance with the recommendations of the World Health Organization to facilitate access to the procedure. In Brazil, despite the problems related to access to legal abortion, its performance remains restricted to hospitals. It is expected to contribute to the reformulation of regulations regarding abortion in the country.